Decade of healthy aging in the Americas: main contributions to public policy formulation (PerCursos, 2025)
The aging process and old age in society are a multifaceted phenomenon, influenced by several factors that shape the quality of life of elderly people. Historically, the perception of the elderly people has fluctuated between veneration and repugnance, however, currently, there is an effort to break stigmas and promote the dignity and social inclusion of this population through public policies. In this context, this study aims to identify the main strategies proposed by the Decade of Healthy Aging in the Americas for the formulation and strengthening of public policies aimed at aging and older people. The study methodology is qualitative and exploratory, using PAHO/WHO documents available on the official website of the Decade of Healthy Aging, which deal with public policies, both in their entirety and in partial forms; as an analysis method, the Content Analysis technique was used. The results highlight two main categories: the strategies for formulating inclusive public policies and the weaknesses that still impede the effectiveness of these policies, such as ageism and barriers to accessing services, spaces and society. The main strategies include transforming perceptions about aging, promoting the capabilities of older people, integrating health services and accessing long-term care. The weaknesses identified include ageist prejudices, difficulties in accessing services and a lack of environments and society that are effectively friendly to older people. Therefore, the need for public policies that consider the multiple specificities of aging is emphasized in order to promote ways of aging actively and healthily, deconstructing social barriers. The inclusion of elderly people must be seen as an essential factor for social and citizen development in the construction of a fairer and more equitable society.
Keywords: elderly person; public policies; inclusion; elderly-friendly cities and communities